Dorsal switch protein 1 as a damage signal in insect gut immunity to activate dual oxidase via an eicosanoid, PGE2 - Roy, Miltan Chandra; Ahmed, Shabbir; Kim, Yonggyun (Frontiers in Immunology, 2022)
Various microbiota including beneficial symbionts reside in insect gut. Infections of pathogens cause dysregulation of the microflora and intimidate the insect survival. Reactive oxygen species (ROS) has been used in the gut immune responses, in which its production is tightly regulated by controlling dual oxidase (Duox) activity via Ca2+ signal to protect beneficial microflora and gut epithelium due to its high cytotoxicity. However, it was not clear how the insects discriminate the pathogens from the various microbes in the gut lumen to trigger ROS production. An entomopathogenic nematode, Steinernema feltiae, infection elevated ROS level in the gut lumen of a lepidopteran insect, Spodoptera exigua. Dorsal switch protein 1 (DSP1) localized in nucleus in the midgut epithelium was released into plasma upon the nematode infection and activated phospholipase A2 (PLA2). The activated PLA2 led to increase of PGE2 level in the midgut epithelium, in which rising Ca2+ signal up-regulated ROS production. Inhibiting DSP1 release by its specific RNA interference (RNAi) or specific inhibitor, 3-ethoxy-4-methoxyphenol, treatment failed to increase the intracellular Ca2+ level and subsequently prevented ROS production upon the nematode infection. A specific PLA2 inhibitor treatment also prevented the up-regulation of Ca2+ and subsequent ROS production upon the nematode infection. However, the addition of PGE2 to the inhibitor treatment rescued the gut immunity. DSP1 release was not observed at infection with non-pathogenic pathogens, but detected in plasma with pathogenic infections that would lead to the damage on the gut epithelium. These results indicate that DSP1 acts as damage-associated molecular pattern in gut immunity through DSP1/PLA2/Ca2+/Duox.